2015
DOI: 10.1002/cta.2072
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic model of direct matrix converter and its experimental validation

Abstract: Summary Power electronics is a major candidate in the ongoing research of electrical power grids because they can provide better control with more information (voltage ratio, efficiency, power flow direction, etc.) than the all‐passive solutions such as transformers and so forth. Power electronic transformer has the possibility to replace the conventional one by ac/ac matrix converter with high‐frequency compact electronic transformers. In this work, a dynamic model of matrix converter is studied and issues su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…On the other hand, the main focus is on power line switching with the aid of power routers. The matrix converter has already been studied through both simulation and experiment from the authors [15]. This is called direct topology and its main difference from the indirect one is the lack of the DC link.…”
Section: Matrix Converter and Power Routermentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, the main focus is on power line switching with the aid of power routers. The matrix converter has already been studied through both simulation and experiment from the authors [15]. This is called direct topology and its main difference from the indirect one is the lack of the DC link.…”
Section: Matrix Converter and Power Routermentioning
confidence: 99%
“…Previous studies have already experimented with a matrix converter [15] and AC conversion [16], and the combination of both in a single apparatus is a natural extension of this research.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As it does not require a large‐capacity electrolytic capacitor in the direct current (DC) link, it also has high power density and high reliability. Due to above advantages, the matrix converter has gained considerable attention from researchers . At present, research on matrix converters mainly focuses on three‐phase‐three‐phase matrix converters (3‐3MCs), including new topologies, control strategies, overmodulation methods, common mode voltage suppression, and fault tolerance .…”
Section: Introductionmentioning
confidence: 99%
“…Algorithms such as predictive control and space vector modulation (SVM) control the modulation of the switches. 5 Recent matrix converters studies on dynamical models are reported in Kordonis and Hikihara 6 ; circuit topologies in Trentin et al, 7 Liu et al, 8 and Mizutani et al 9 Furthermore, Siami et al 10 At the boundary of straightforward research, unexpected behavior is disregarded without actually going into an in-depth analysis of the cause. 5 Nevertheless, characteristics of MCs such as a compact power circuit (no DC-link capacitor) and sinusoidal input and output currents make the MC an interesting research topic.…”
Section: Introductionmentioning
confidence: 99%